El Niño-Southern Oscillation, rainfall, temperature and Normalized Difference Vegetation Index fluctuations in the Mara-Serengeti ecosystem - Ogutu, J.; Piepho, Hans-Peter; Dublin, H.T.; Bhola, N.; Reid, Robin S. (Wiley, 2008)
Understanding long-term climatic variability is basic to wise management and conservation of biodiversity. We analysed temporal variations in the local rainfall, temperature, Normalized Difference Vegetation Index and the hemispheric El Nin˜ o-Southern Oscillation (ENSO), using the Southern Oscillation Index and how they co varied in the Mara-Serengeti ecosystem of Kenya and Tanzania. Local rainfall showed a striking temporal variability and an evident 5-year quasi-periodicity in the ecosystem. Severe droughts were a recurrent ⁄ persistent feature of the ecosystem but extreme floods were relatively infrequent. The timings of droughts and floods coincided with strong episodes in the activities of the ENSO phenomenon. Above-average rainfall often accompanied cold ENSO episodes and below-average rainfall warm ENSO events, contrary to past generalizations suggesting that warm ENSO events are only associated with above-average rainfall whereas cold ENSO events with below-average rainfall in equatorial East Africa. Both minimum and maximum temperatures were below-normal during cold ENSO episodes and above-normal during warm ENSO events. Rising temperatures and declining rainfall throughout the 1990s and early 2000s, with unprecedently prolonged and strong ENSO episodes, engendered progressive habitat desiccation and reduction in vegetation production in the ecosystem. This exacerbated the debilitating effects of adverse weather on local plant and animal communities, resulting in high mortalities of ungulates.